2014
DOI: 10.1007/s00234-014-1344-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of irradiated brain metastases using dynamic contrast-enhanced magnetic resonance imaging

Abstract: SRS was associated with a reduction of K trans values of the cerebral metastases in the early post-treatment period. Furthermore, K trans variation as assessed using DCE MRI may be helpful to predict midterm outcomes after SRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…In one study, lower Ktrans and lower relative CBF (rCBF) at 1 week after treatment correlated with responders, whereas higher rCBF and rCBV at 4 weeks were associated with therapy benefit (Jakubovic et al, 2014). Another study also analyzed Ktrans data and found that even a small increase in Ktrans at 4–8 weeks after SRS was associated with tumor progression (Almeida-Freitas et al, 2014), similar to a prior analysis that found that increased CBV at 6 and 12 weeks is associated with worse outcome (Fig. 7.5) (Essig et al, 2003).…”
Section: Early Response Markerssupporting
confidence: 64%
“…In one study, lower Ktrans and lower relative CBF (rCBF) at 1 week after treatment correlated with responders, whereas higher rCBF and rCBV at 4 weeks were associated with therapy benefit (Jakubovic et al, 2014). Another study also analyzed Ktrans data and found that even a small increase in Ktrans at 4–8 weeks after SRS was associated with tumor progression (Almeida-Freitas et al, 2014), similar to a prior analysis that found that increased CBV at 6 and 12 weeks is associated with worse outcome (Fig. 7.5) (Essig et al, 2003).…”
Section: Early Response Markerssupporting
confidence: 64%
“…For example, Almeida-Freitas et al studied a mixed-histology cohort of 26 patients with 34 BMs treated with SRS. 30 All patients were treated with SRS and then reimaged 4-8 weeks after therapy. The researchers found that an increase of 15% in K trans after SRS was significantly predictive of tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Quite similarly, Cao et al 25 investigating the effect of radiation therapy on the blood-brain barrier permeability of primary brain tumours using dynamicenhanced MRI noted a gradual decrease of K trans as soon as 1 month after the treatment. More recently, Almeida-Freitas et al 26 reported a significant reduction in K trans values of cerebral metastasis 4-8 weeks after stereotactic radiosurgery. An increase of one or both parameters at the beginning of treatment should not be misinterpreted as increasing resistance.…”
Section: Discussionmentioning
confidence: 97%